Meningkatkan Kemampuan Membaca Permulaan dengan Media Kartu Huruf pada Siswa Kelas II Sekolah Dasar - Waridah Waridah; Irsa Irmayanti; M. Akip (Medan Resource Center, 2023)
The study was motivated by the low initial reading ability of students. The purpose of this research was to determine the improvement of students' initial reading skills using letter card media. The research employed a classroom action research method with grade II B students as the subjects. The object of the study was the students' initial reading ability through the implementation of letter card learning media. Data collection techniques included tests, observation, and documentation. The research instruments consisted of oral tests, checklist sheets, and observation sheets. The results of the study revealed that the use of letter card media significantly improved the initial reading skills of grade II B students at SD Negeri 19 Tanjung Tengang. The completion rate of students in cycle 1 was 54.16%, and in cycle II, it increased to 87.50%. The significant percentage increase from cycle I to cycle II led to the conclusion that students' initial reading skills can be effectively enhanced through the implementation of letter card media.